(untitled) (Architecture Image Studies, 2026)
The research highlights the increasing importance of international electronic commerce as a modern form of global exchange, demonstrating its potential to enhance trade efficiency and connectivity across borders. The study also examines the evolution of China’s foreign economic policy, identifying its strategic shifts and assessing their impact on trade relations with Central Asian countries.A detailed analysis of China’s trade with Central Asian nations reveals key trends, challenges, and opportunities in bilateral and multilateral economic cooperation. The study further evaluates the role of the Belt and Road Initiative (BRI) as a transformative force in regional and global trade, emphasizing its contribution to infrastructure development and trade facilitation.